2013
DOI: 10.2478/bvip-2013-0068
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-4, but not toll-like receptor-2 mediates secretion of tumour necrosis factor α and interleukin-8 in lipopolysaccharide-stimulated mouse mammary epithelial cells

Abstract: Mammary epithelial cells (MECs) from Kunming mice were isolated and stimulated in vitro with 10 μg/mL of Escherichia coli lipopolysaccharide (LPS). The release of tumour necrosis factor α (TNF-α) and interleukin-8 (IL-8) into culture supernatants was measured by ELISA. Furthermore, blocking experiments with Toll-like receptor 2 (TLR2) and TLR4 antibodies were performed to verify whether cytokine secretion depended on LPS-induced activation of TLR2 or TLR4. The results revealed that LPS-stimulated mouse MECs si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This was found by Pareek et al (23) and Wellnitz and Kerr (33). In our previous laboratory study (8), we found that mouse MECs can respond to the presence of LPS (10 μg/mL) and significantly up-regulate the release of TNF-α and IL-6. Using the LPS-stimulated infection model, we investigated the effect of JYT addition to the LPS-stimulated culture on production of TNF-α and IL-6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was found by Pareek et al (23) and Wellnitz and Kerr (33). In our previous laboratory study (8), we found that mouse MECs can respond to the presence of LPS (10 μg/mL) and significantly up-regulate the release of TNF-α and IL-6. Using the LPS-stimulated infection model, we investigated the effect of JYT addition to the LPS-stimulated culture on production of TNF-α and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for primary culture of MECs has been previously described (8). In brief, mammary tissue was isolated from midpregnancy mice, and epithelial cells were obtained after mixed protease digestion of the tissue.…”
Section: Reagentsmentioning
confidence: 99%